2022
DOI: 10.1186/s12883-022-02705-2
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal brain functional and structural connectivity between the left supplementary motor area and inferior frontal gyrus in moyamoya disease

Abstract: Background Disruption of brain functional connectivity has been detected after stroke, but whether it also occurs in moyamoya disease (MMD) is unknown. Impaired functional connectivity is always correlated with abnormal white matter fibers. Herein, we used multimodal imaging techniques to explore the changes in brain functional and structural connectivity in MMD patients. Methods We collected structural images, resting-state functional magnetic res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Impairment in functional connectivity in patients with symptomatic MMD has been demonstrated in resting-state functional MRI studies [2][3][4]. With the enhanced awareness of physical examination and advances in noninvasive magnetic resonance methods, the early detection of asymptomatic patients with MMD who have not experienced CVAs is possible [5].…”
Section: Introductionmentioning
confidence: 99%
“…Impairment in functional connectivity in patients with symptomatic MMD has been demonstrated in resting-state functional MRI studies [2][3][4]. With the enhanced awareness of physical examination and advances in noninvasive magnetic resonance methods, the early detection of asymptomatic patients with MMD who have not experienced CVAs is possible [5].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that progression of the MMD can cause damage to the brain regions responsible for speech and language, leading to a variety of dysfunctions. In particular, the disease has been associated with damage to the frontal and temporal lobes, which play key roles in speech production and comprehension (Hu et al, 2022;Saito et al, 2021). The study by Zuo and colleagues showed that nearly 30% of patients (in a sample of 142 individuals) with moyamoya disease had speech impairments in the form of dysarthria and aphasia (Zuo et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…A 'network pathophysiological model' of dystonia has been proposed, in which multiple lesions in and outside the basal ganglia and defective interactions among different nodes in the motor network can produce dystonia [25]. In addition, abnormal inhibitory control of the motor cortex from the frontal cortex suppression frontal was found in various diseases [26]. Therefore, the present study hypothesized changed role of the frontal regions in the motor network might be related to the etiology of Meige and the main difference between these two disorders.…”
Section: Introductionmentioning
confidence: 99%